The impact of nitrogen concentrations on production and quality of food and feed supplements from three cyanobacteria and potential application in biotechnology. (March 2020) - Issa, Ahmed; Ali, Esmat; Abdel-Basset, R.; Awad, M.F.; Ebied, A.M.; Hassan, S.A.
Abstract: Primary metabolites (carbohydrates, proteins and amino acids) as well as growth and total dry mass displayed species and nitrogen dose dependency. Secondary metabolites, namely, phycobilins (contents and fractions) and lipids (contents and fractions) were also variably altered in the studied organisms. Three strains of cyanobacteria were isolated, purified and identified using the morphological approach and confirmed using 16S r- RNA. Namely, Anabaena sp., Merismopedia tenuissima and Arthrospira ( Spirulina ) platensis were cultivated under various nitrogen concentrations. Growth curves were followed for 14 days using chlorophyll (Chl.) a contents, which showed a gradual increase with time till the 12 th day (stationary phase started); after that Chl. a contents were sharply decreased. Nitrogen deficiency enhanced growth (Chl. a, dry weight and rate) of Anabaena, Merismopedia and Arthrospira in comparison with the control (100% N), may be due to their coherent ability to fix atmospheric nitrogen. However, 100% nitrogen deficiency decreased growth of the three studied cyanobacteria, probably indicating insufficiency of nitrogen fixation to fulfill their cellular needs. Photosynthesis and respiration as the source as influenced by nitrogen availability as the sink were also concerned with in this work.